Forest supports living on earth: awareness of the youth at Jembrana Regency Bali Province Indonesia - Ni Made Ernawati; I Wayan Basi Arjana; Nyoman Mastiani Nadra (Politeknik Negeri Bali, 2021)
Locals awareness of the importance of forest in sustaining the earth plays an important role in the success of forest conservation. Using forest as an agricultural area without depriving its main function requires awareness of the farmers including the people living around the forest. This study examines the level of awareness of the Youth at Jembrana Regency particularly the elementary, junior high and senior high school students regarding the importance of forest supporting living on earth. This research is a qualitative study exploring the response of the youth to a question: how forest support living on earth? The results indicate three types of awareness: 1) Fully aware of the function of the forest and a harmonious co-exist with forest farmers, 2) Forest for economic benefit, and 3) Only focus on forest issues and conservation. It is expected that the study results could become a reference for people, organization and relevant authority concern regarding the forest conservation particular in Jembrana Regency.